Environmental cephalosporin-resistant gram-negative bacteria: what is lurking beyond the hospital doors? - Yusuf, Yasna; Awoyomi, Olubosede; Bradbury, Alison; Wang, Yongsheng; Episcopia, Briana; Abdallah, Marie; Quale, John (International Journal of Infection Control, 2025)
Antibiotic resistant Gram-negative bacilli are being increasingly recognized in community-onset infections. Concerns have been raised regarding environmental surfaces as reservoirs for multidrug-resistant pathogens; in particular, community wastewater samples have been found to harbor cephalosporin- and carbapenem-resistant Enterobacterales. In this report, we used selective media to culture cephalosporin-resistant Gram-negative bacilli from high-touch surfaces in the environment surrounding hospitals in New York City. Of the 336 surfaces swabbed, 66 grew cephalosporin-resistant Gram-negative bacteria. No Enterobacterales were isolated. The most common isolate was Brucella (Ochrobactrum) spp., accounting for 26 of the 66 positive cultures; 19 originated from surfaces near two hospitals. One isolate of Brucella (Ochrobactrum) spp. was found to possess blaOXA-24. Acinetobacter spp. accounted for 12 of the 66 positive cultures. Forty cultures obtained with saline-saturated gauze were obtained at public transportation centers near hospitals; a comparable 40 cultures were obtained at transportation centers distant from hospitals. Of the 38 positive cultures from transportation surfaces near medical centers, 15 grew Brucella (Ochrobactrum) spp. In comparison, Brucella (Ochrobactrum) spp. accounted for only five of the 33 positive transportation cultures distant from medical centers (P = 0.03). Again, none of the cultures grew Enterobacterales. It is reassuring that dried environmental surfaces around hospitals did not contain resistant Enterobacterales. However, Brucella (Ochrobactrum) spp. was widespread and territorial and may be a reservoir for OXA-type carbapenemases.